INOCULAÇÃO DE LEVEDURA E BACTÉRIA EM CAFÉ CONILON (COFFEA CANEPHORA) PROCESSADO POR VIA ÚMIDA - Bravim, Danielle Gonçalves (2021)
The state of Espírito Santo is the largest national producer of conilon coffee. Consumers' search for coffees with different profiles has driven research aimed adding value to the drink. Induced fermentation can favor positive sensory attributes, valuing coffee, but studies involving Coffea canephora are still scarce. This study aimed to evaluate the impact of inoculation of a yeast (Meyerozyma guilliermondii), a bacteria (Bacillus licheniformis) and the two species in co-culture in wet processed conilon coffee, quantifying the microbial groups, acids, sugars and volatile compounds at different times of fermentation, as well as the effects caused by these compounds on the quality of the beverage. For this, four treatments were carried out and inoculated with Bacillus licheniformis (CCMA 1673), Meyerozyma guilliermondii (CCMA 1740) and the two species in co-culture. Wet fermentation was carried out for 48 hours in polyethylene buckets. Subsequently, the coffees were dried on terraces suspended under sun exposure until they reached a water content of 11% b.u. Samples were collected throughout the fermentation period at 0, 24, and 48 hours for enumeration of mesophilic bacteria, lactic acid bacteria, yeasts and filamentous fungi. Organic acids and sugars (HPLC) were identified and quantified throughout fermentation and volatile compounds (GC-MS) were analyzed before and after roasting. Cup tasting with certified tasters was carried out following the fine robusta tasting protocol. The inoculation of MG and BL stimulated the multiplication of lactic acid bacteria, differing from the CON and MB treatments, at the end of fermentation. Acetic, citric, lactic, oxalic, malic, succinic and tartaric acids were identified in all treatments at different concentrations. The acetic acid concentration was higher for the BL treatment at 24h and 48h times, differing from the other treatments. The mean concentration of fructose ranged between 4.0 and 10.9 mg/g between samples and glucose between 0.2 and 2.7 mg/g. There was a reduction in these sugars during fermentation, except for MB. 2-Heptanol, 2-Nonanol, heptanone and methyl salicylate were found during fermentation and can impart woody, fruity and nutty aromas to beverage. Methylpyrazine, 2,6-dimethylpyrazine, 2,5-dimethylpyrazine, 3-ethyl-2,5- dimethylpyrazine identified after roasting give to the drinks “almond” and “chocolate” notes identified by the tasters in the cupping. All treatments were classified as “Premium” with the highest score given to the BL treatment. Bacillus licheniformis performed better under the wet fermentation, leading to an increase in the coffee score and the production of volatile compounds that add positive sensory notes to the beverage. Thus, the use of this bacteria is beneficial in the wet fermentation of conilon coffee.